2017
DOI: 10.7150/ijms.20809
|View full text |Cite
|
Sign up to set email alerts
|

IL-36γ inhibits differentiation and induces inflammation of keratinocyte via Wnt signaling pathway in psoriasis

Abstract: Psoriasis is a common inflammatory skin disease characterized by abnormal keratinocyte inflammation and differentiation that has a major impact on patients' quality of life. IL-36γ, a member of IL-36 cytokine family, is highly expressed in psoriasis and plays an important role in inflammation response and differentiation. However, the function of IL-36γ in differentiation and inflammation of keratinocyte in psoriasis has not been clearly identified. Thus, this study aimed to investigate the role of IL-36γ on d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
56
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 31 publications
(41 reference statements)
8
56
0
2
Order By: Relevance
“…Similarly, the inhibition of β‐catenin restricts IL‐22‐induced keratinocyte proliferation by downregulating the expression of Wnt target genes . The treatment of HaCaT cells with IL‐36γ induces an increase in the expression levels of β‐catenin, cyclin D1, and Ki‐67, which may contribute to the hyperproliferation of keratinocytes in psoriasis . Therefore, the inhibition of Wnt/β‐catenin signalling may be a potential therapeutic option for psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the inhibition of β‐catenin restricts IL‐22‐induced keratinocyte proliferation by downregulating the expression of Wnt target genes . The treatment of HaCaT cells with IL‐36γ induces an increase in the expression levels of β‐catenin, cyclin D1, and Ki‐67, which may contribute to the hyperproliferation of keratinocytes in psoriasis . Therefore, the inhibition of Wnt/β‐catenin signalling may be a potential therapeutic option for psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…The role of IL‐36γ in psoriasis pathogenesis is increasingly recognized . Previous reports have shown that IL‐36γ induced proinflammatory mediators, as well as proliferation in keratinocytes . In this study, we hypothesized that dsRNA and IL‐17A–mediated innate immune response resulted in the acute exacerbation of inflammatory phenotype of keratinocytes, by synergistically enhancing expression of IL‐36γ.…”
Section: Introductionmentioning
confidence: 93%
“…[17][18][19] Previous reports have shown that IL-36γ induced proinflammatory mediators, as well as proliferation in keratinocytes. [13,20,21] In this study, we hypothesized that dsRNA and IL-17A-mediated innate immune response resulted in the acute exacerbation of inflammatory phenotype of keratinocytes, by synergistically enhancing expression of IL-36γ. The subsequent mechanistic study revealed a crucial role for the transcriptional co-factor IκBζ in dsRNA/IL-17A-provoked synergistic effects in keratinocytes.…”
mentioning
confidence: 99%
“…Therefore, exosomes probably play an immunomodulatory role in the CC microenvironment. The pro‐inflammatory cytokine, IL‐36γ, has the ability to induce inflammation in keratinocytes via the Wingless/integrase 1 signaling pathway . Rana and colleagues demonstrated the presence of IL‐36γ inside exosomes derived from polyinosinic:polycytidylic acid (poly(I:C))‐treated keratinocytes.…”
Section: The Relationship Between Exosomes Inflammation and Cervicalmentioning
confidence: 99%